Fasting‐induced liver GADD45β restrains hepatic fatty acid uptake and improves metabolic health - Fuhrmeister, Jessica; Zota, Annika; Sijmonsma, Tjeerd P.; Seibert, Oksana; Guia, Roldan M. de; Niopek, Katharina; Berriel Diaz, Mauricio; Okun, Jürgen G.; Herzig, Stephan; Rose, Adam J. (EMBO molecular medicine, 2016)
Recent studies have demonstrated that repeated short‐term nutrient withdrawal (i.e. fasting) has pleiotropic actions to promote organismal health and longevity. Despite this, the molecular physiological mechanisms by which fasting is protective against metabolic disease are largely unknown. Here, we show that, metabolic control, particularly systemic and liver lipid metabolism, is aberrantly regulated in the fasted state in mouse models of metabolic dysfunction. Liver transcript assays between lean/healthy and obese/diabetic mice in fasted and fed states uncovered “growth arrest and DNA damage‐inducible” GADD45β as a dysregulated gene transcript during fasting in several models of metabolic dysfunction including ageing, obesity/pre‐diabetes and type 2 diabetes, in both mice and humans. Using whole‐body knockout mice as well as liver/hepatocyte‐specific gain‐ and loss‐of‐function strategies, we revealed a role for liver GADD45β in the coordination of liver fatty acid uptake, through cytoplasmic retention of FABP1, ultimately impacting obesity‐driven hyperglycaemia. In summary, fasting stress‐induced GADD45β represents a liver‐specific molecular event promoting adaptive metabolic function. Synopsis: Fasting is shown to induce liver GADD45β, which functions as an adapter protein to retain FABP1 in the cytoplasm and restrain fatty acid uptake. The blunting of GADD45β induction occurring in obesity/aging may explain the altered lipid metabolism. An altered lipid metabolism signature is especially apparent in the fasted state of obese and aged mice.Fasting induction of GADD45β is blunted in the liver of obese/aged mice and T2D humans.During fasting, liver GADD45β controls systemic and hepatic lipid handling via cytoplasmic FABP1 retention.Liver GADD45β expression improves glucose homoeostasis in obesity.